Optimized Attenuated Salmonella Typhimurium Suppressed Tumor Growth and Improved Survival in Mice - Liang, Kang; Zhang, Rui; Luo, Haiyan; Zhang, Jinlong; Tian, Zhenyuan; Zhang, Xiaofen; Zhang, Yulin; Ali, Md Kaisar; Kong, Qingke (Frontiers in Microbiology, 2021)
The gram-negative facultative anaerobic bacteria Salmonella enterica serovar Typhimurium (hereafter S. Typhimurium) has always been considered as one candidate of anti-tumor agents or vectors for delivering drug molecules. In this study, we compared several widely studied S. Typhimurium strains in their anti-tumor properties aiming to screen out the best one for further optimization and use in cancer therapy. In terms of the motility, virulence and anti-tumor efficacy, the three strains 14028, SL1344 and UK-1 were similar and obviously better than LT-2, and UK-1 showed the best phenotypes among them. Therefore, the strain UK-1 (D) was selected for the following studies. Its auxotrophic mutant strain (D1) harboring ∆aroA and ∆purM mutations was further optimized through the modification of lipid A structure, generating a new strain named D2 with stronger immunostimulatory activity. Finally, the ∆asd derivative of D2 was utilized as one live vector to deliver anti-tumor molecules including the angiogenesis inhibitor endostatin and apoptosis inducer TRAIL and the therapeutic and toxic-side effects were evaluated in mouse models of colon carcinoma and melanoma. After intraperitoneal infection, engineered Salmonella bacteria equipped with endostatin and/or TRAIL significantly suppressed tumor growth and prolonged survival of tumor-bearing mice compared to PBS or bacteria carrying the empty plasmid. Consistently, immunohistochemical studies confirmed the colonization of Salmonella bacteria and the expression of anti-tumor molecules inside tumor tissue, which were accompanied by the increase of cell apoptosis and suppression of tumor angiogenesis. These results demonstrated that the beneficial anti-tumor efficacy of attenuated S. Typhimurium bacteria could be improved through delivery of drug molecules with powerful anti-tumor activities.